Особливості художнього трактування антитоталітарних ідей у романах Валентина Тарнавського «Порожній п'єдестал» і «Матріополь» - Змінчак, Наталія; Zminchak, Natalia (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття присвячена аналізу романів В. Тарнавського у світлі тематології. Спеціально простежується антитоталітарний контекст творчості прозаїка, що в ідейно-художньому ключі активно демонструє процес взаємин особистості та влади. The article is devoted to the analysis of V. Tarnavskiy's novels in terms of tematology. Especially traced antytolitarian context of creativity of the writer that in ideological and artistic vein actively demonstrates the relationships of personality and Soviet council. Such features as conformity, passivity, mistrust and detachment from the environment, loss of national roots and identity, split soul, by folowing the novelistic logic of the writer, deeply rooted in human nature of post-totalitarian world. Exposing them in satirical passages, Valentine Tarnavskyi artisticly confirmed that with the collapse of the Soviet Union we didn't get rid of those rudiments, and the same type of people thrives in the newly created state. In the subtext of novels incorporated the idea of the necessity of creating a new discourse, Ukrainian, national, deprived of chimeras with Soviet quality. Resorting to the comparative analysis we trace the evolution from social issues in the first novel to a deepening of the internal psychological aspects of the life and work of an individual in a totalitarian society in «The Matriopol».
The Features of Artistic Interpretation of Anti-totalitarian Ideas in Valentine Tarnavskiy's Novels «The Empty Pedestal» and «Matriopol»
Keywords: поколение восьмидесятников; Валентин Тарнавский; eightiers generation; Valentin Tarnavskiy